Inpatient Dignity Scale: Mandarin translation and psychometric characteristics evaluation - Yao Huang; Ying Zhou; Thomas Kwok Shing Wong; Dongyi Luo; Gangna Zhang; Jiani Chen; Graeme D. Smith (Wiley, 2022)
Abstract Aim The aim of this paper was to translate the English version of the Inpatient Dignity Scale into Mandarin and to test the psychometric properties of the Mandarin version of the Inpatient Dignity Scale. Design This research is a cross‐sectional survey, using convenience sampling. Methods The English version of the Inpatient Dignity Scale was translated into Mandarin Chinese. From June-August 2020, 736 inpatients from 50 tertiary hospitals in Guangzhou were recruited to assess the psychometric attributes of the Inpatient Dignity Scale. Results The Mandarin version of the Inpatient Dignity Scale consists of expectation and satisfaction subscales. It differs from the English language version, as the expectation subscale includes three dimensions and the satisfaction subscale includes two dimensions. The total Cronbach alpha coefficient of the expectation subscale and the satisfaction subscale were .820 and .965, respectively, and the split‐half reliability of the expectation subscale and the satisfaction subscale were 0.740 and 0.928, respectively, indicating good internal consistency and effectiveness. Known‐groups validity was established, as 70% of the hypotheses were supported.